2016
DOI: 10.1007/978-3-319-42970-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Fathers on Leave Alone in Spain: ‘Hey, I Want to Be Able to Do It Like That, Too’

Abstract: Spain underwent the transition from the male breadwinner to the dual-earner family model somewhat later than other developed countries. Change was most intense in the period of strong economic and employment growth between 1995 and 2007, with a reversal observed as unemployment rose from early 2008. The percentage of 25-to 49-year-old women in paid employment climbed from 39 % in 1995 to 66 % in 2007, receding to 61 % in 2012. As a result of the employment crisis, while male single-earner families with childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
0
15
0
7
Order By: Relevance
“…al, 2015;González and Jurado, 2015). Studies on single parenting noted the skills that are put in practice in the exercise of fatherhood, as well as the sense of responsibility and the links between fathers and children derived from parenting (Avilés Hernán-dez, 2015;Meil et al, 2016). One of the few studies analysing fatherhood in Spain using focus groups was that of Alberdi and Escario (2007).…”
Section: Recent Research On Fatherhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…al, 2015;González and Jurado, 2015). Studies on single parenting noted the skills that are put in practice in the exercise of fatherhood, as well as the sense of responsibility and the links between fathers and children derived from parenting (Avilés Hernán-dez, 2015;Meil et al, 2016). One of the few studies analysing fatherhood in Spain using focus groups was that of Alberdi and Escario (2007).…”
Section: Recent Research On Fatherhoodmentioning
confidence: 99%
“…Los primeros concluyen que unos recursos materiales parecidos en el seno de la pareja, así como unos valores de género igualitarios, terminan siendo elementos clave en una futura división igualitaria de los cuidados (Abril et al, 2015; González y Jurado, 2015). En los segundos se señalan las habilidades que se ponen en práctica en el ejercicio de la paternidad, así como el sentido de responsabilidad y los vínculos entre padres e hijos derivados de dicha actividad (Avilés Hernández, 2015;Meil et al, 2016). Una de las pocas investigaciones donde se analiza la paternidad en España mediante grupos de discusión es la de Alberdi y Escario (2007).…”
unclassified
“…Scant information is available on the impact of leave-taking at the workplace, however. Qualitative studies have shown, in the case of men taking parental leave, that workmates' most frequent reaction is indifference, although occasionally attendant upon surprise and joking about the idea (Meil et al, 2017a, RomeroBalsas, Rogero-García, 2017aWall, 2014). Further to the survey results analysed, only 5 % of those using a leave reported any objection or attempted discouragement by their workmates.…”
Section: Number Of Cases 74 269 343mentioning
confidence: 99%
“…However, at the same time we can talk of the emergence of the ideal of a "new father" (Bonney et al, 1999;Devreux, 2007;Fursman and Callister, 2009;Fox et al, 2009;O'Brien and Moss, 2010;Gregory and Milner, 2011;Romero-Balsas et al, 2013;Meil et al, 2017a;Meil et al, 2017b), who is a direct and involved carer of their children. O'Brien and Moss, referring to the case of Europe, state that "today fathers are expected to be accessible and nurturing as well as economically supportive to their children".…”
Section: "New Fathers"mentioning
confidence: 99%